Debonding of bonded composite joints with TEP modified epoxy adhesives - Caglar, Hasan (2023)
Prevention of mechanical and thermal damage to the composite parts is crucial during the debonding process of adhesive joints. This work highlights the impact of thermally expanded particles (TEPs) on bulk adhesive properties and the lap shear strength of adhesively bonded GFRP joints. FTIR studies revealed insignificant chemical changes occurring among the epoxy and its blend with TEPs. The addition of TEPs has slightly influenced the glass transition temperature (Tg) of adhesive. TMA showed that TEPs lose permanent expansion above maximum expansion temperature due to burst and/or diffuse of gas through the thin shell. DIC analysis of materials revealed that CTE mismatch grows with the addition of TEPs in x and y directions. Increases in TEP content up to 15 wt.% also raised the maximum dimension change in the epoxy adhesive. DMA and TGA studies indicated no major change in storage modulus and weight loss when GFRP was heated up to 170°C. The contact angle of GFRP decreased substantially after plasma surface treatment. Plasma surface treatment provided higher bond strength at room temperature than sandblasting surface treatment and prevented fiber-tearing. Despite the incorporation of TEPs, the enhanced debonding effectiveness at 145°C was marginal (less than 5%) for the epoxy adhesive used in the study. The incorporation of TEPs generated the residual stresses inside the adhesive as confirmed by measuring the residual strength of SLJ samples, especially 10 wt.% TEPs-epoxy joints exhibited more than 20% strength drop.